FORMULASI DAN EVALUASI SEDIAAN LIP BALM DENGAN PEWARNA EKSTRAK UBI JALAR UNGU (Ipomoea batatas (L.) Lamk.) - Supartiningsih, Supartiningsih; Sitorus, Elly Nurita; Silalahi, Yosy Cinthya Eriwaty; Khairunnisa, Khairunnisa (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Lip balm is a cosmetic preparation with the main components such as wax, fat, and oil from natural or synthesized extracts with the aim of preventing dryness of the lips by increasing lip moisture and protecting the adverse effects of the environment on the lips. The use of purple sweet potato as a dye is because purple sweet potato (Ipomoea batatas (L.) Lamk.) has an attractive color, the color of purple sweet potato is due to the presence of anthocyanin pigments which are derivatives of flavonoid compounds which are generally soluble in polar solvents. This study aims to formulate and evaluate lip balm preparations using purple sweet potato extract at concentrations of 3%, 6%, 9%, and without using purple sweet potato extract. This research is experimental research. Lip balm preparations were made by adding purple sweet potato extract with various concentrations (F1) 3%, (F2) 6%, (F3) 9%, and blank formula (F0) as the basis for lip balm preparations without purple sweet potato extract. Evaluation of the preparation includes homogeneity test, stability test, smear test, adhesion test, spreadability test, and pH test. The test results showed that purple sweet potato extract can be formulated in lip balm preparations that have a homogeneous composition, have good smearing power, good adhesion F0 (1 minute), F1 (1 minute 3 seconds), F2 (1 minute 8 seconds). seconds), F3 (1 minute 11 seconds), spreadability (5-5.7cm), pH test on all preparations showed a pH that was in accordance with the pH of the skin. And obtained formula 3 is the best formula.